Pengaruh Pemberian Ultrasound Therapy, Wrist Stretching dan Tendon Gliding Exercise pada Kondisi Carpal Tunnel Syndrome Dextra : Laporan Kasus - Dwi Rosella Komalasari; Leo Muchamad Dachlan; Serina Laurenza Putri Rianto; Dian Lestari (STIKes Ibnu Sina Ajibarang, 2024)
Introduction: Carpal Tunnel Syndrome is a stretch of the median nerve caused by pressure on the median nerve in the carpal tunnel when the nerve passes through the tunnel. So that pain, paraesthesia, and numbness appear in the area through which the median nerve passes. Purpose: This case report was aimed to determine the effect of physiotherapy interventions in the form of Ultrasound Therapy, Wrist Stretching, and Tendon Gliding exercise on a female patient aged 66 years. Method: A Case report was conducted 3 times over two weeks by evaluating pain using the Numeric Rating Scale (NRS), a wide range of motion using a goniometer, and the patient’s functional activity using the DASH questionnaire. Result: There was a decrease in motion pain from the value of the NRS scale 6 to the NRS scale 4, and tenderness from the value of the NRS scale 2 to the NRS scale 1. An increase in the range of motion of the joint in dorsiflexion and active palmar flexion movements from T1 (S: 40̊ - 0̊ - 45̊) to T3 (S: 40̊ - 0̊ - 45̊), in the active radial and ulnar deviation movements from T1 (F: 15̊ - 0̊ - 20̊) to T3 (F: 15̊ - 0̊ - 25̊). Functional improvement in patients with DASH results from 61 to 50. Conclusion: The effects of ultrasound therapy, wrist stretching, and tendon gliding exercises are that they can reduce pain, increase ROM, and increase functional activity in patients with carpal tunnel syndrome.